Effects of aerobic and resistance training on walking and balance abilities in older adults with Parkinson’s disease: A systematic review and meta-analysis - Huishan Song; Sheng Ge; Ji Li; Chendao Jiao; Linghua Ran (PLoS ONE, 2025)
Objective To explore the impact of aerobic and resistance training on walking and balance abilities (UPDRS-III, Gait Velocity, Mini-BESTest, and TUG) in individuals with Parkinson’s disease (PD). Method All articles published between the year of inception and July 2024 were obtained from PubMed, Embase, and Web of Science. Meta-analysis was conducted with RevMan 5.4. Result Research from 15 randomized controlled trials, comprising 792 older patients with a diagnosis of PD, was included in the analysis. Aerobic training (AT) and Resistance training (RT) significantly improved UPDRS-III (AT, SMD = -5.69, 95% CI: -8.67 to -2.71, p = 0.0002, I2 = 82%; RT, SMD = -3.01, 95% CI: -4.89 to -1.12, p = 0.002, I2 = 0%) and Gait Velocity(AT, SMD = 0.88, 95% CI: 0.58 to 1.18, p < 0.00001, I2 = 42%; RT, SMD = 0.52, 95% CI: 0.10 to 0.94, p = 0.01, I2 = 55%). AT showed no difference in Mini-BESTest (AT, SMD = 2.12, 95% CI: -0.70 to 4.94, p = 0.14, I2 = 90%). RT showed no change in TUG (RT, SMD = -0.03, 95% CI: -1.60 to 1.54, p = 0.97, I2 = 63%). Conclusions Resistance training stood out as the most effective approach to boost performance on the mini-BESTest. Conversely, aerobic exercise proved to be superior for improving the UPDRS-III, gait velocity and TUG scores.